(untitled) (Journal of the College of Basic Education, 2026)
Science fiction literature is a genre of writing with a specific audience, possessing formal characteristics that make it receptive to the reader. It addresses their concerns and their many changing worlds. Therefore, studies dealing with this literary field are almost entirely new in Morocco, with a discrepancy between scarcity and rarity in the Maghreb. Moroccan literature needs a literature that stands in between, one that is both clear and tinged with mystery, to enable readers to recognize the next phase, which is filled with ambiguity. It is important for criticism to keep pace with creativity, and for creativity to do the same in turn. They are like two dancers whose steps intertwine, with no way of knowing which one has the advantage of precedence or which one moves the other. It is a complex, dialectical, reciprocal movement.